Measurements of 2-D flow parameters around rectangular prisms arranged at the ground - Błazik-Borowa, Ewa; Bęc, Jarosław; Nowicki, Tomasz; Lipecki, Tomasz; Szulej, Jacek (Budownictwo i Architektura / Civil and Architectural Engineering, 2008)
Measurements of 2-D flows around a square and a rectangle (ratio 2:1) in wind tunnel have been presented in this paper. The results of these measurements presented here are pressure and standard deviation distributions on the models’ walls, components of velocity vectors and statistical moments for fluctuations of velocity in the wind tunnel measuring space. The values of parameters have been presented in graphs and subsequently used in a comparative analysis of the flows around both models.